Can Gaming Get You Fit? - Berg, Jonathan; Wang, Alf Inge; Lydersen, Stian; Moholdt, Trine (Frontiers in Physiology, 2020)
Rationale: Exergaming may be a viable alternative to more traditional exercise. As high-intensity exercise can provide substantial health benefits, the purpose of this study was to investigate the long-term effectiveness of providing inactive adults with access to a high-intensity exergaming platform. Methods: In this single-centre, randomised controlled trial, 52 inactive adults (<150 min of exercise per week), aged 18 years or older, were randomised (1:1) into an exergaming (N = 27) or a control group (N = 25). Exergaming participants were given access to the Playpulse exergaming platform for 6 months, where they decided how frequently they wanted to use the platform. The primary outcome measure, analysed with a mixed model, was peak oxygen uptake (V̇O2peak). Secondary outcomes included body composition, blood pressure, and blood markers of cardiometabolic health. Results: Mean V̇O2peak at 6 months was 42.3 (SD 7.0) mL.kg-1.min-1 and 41.9 (SD 7.4) mL.kg-1.min-1 for the exergaming and control group, respectively with no significant between-group differences (-0.7, 95% CI -2.7 to 1.3, P = 0.49). Apart from increased moderate-intensity physical activity in the exergaming group at 3 months (21.9 min.day-1, 95% CI: 2.2 to 41.5, P = 0.03) compared to the control group, there were no significant between-group differences for any outcome at either 3 or 6 months. On average, participants in the exergaming group performed 12 (SD 13) exergaming sessions with an average heart rate of 74.5 (SD 7.5) % of max heart rate, throughout the intervention. Conclusion: Due to low exergaming frequency over the 6-month intervention, exergaming participants showed no significant health benefits compared to control. Our study indicates that although the Playpulse exergaming platform is found enjoyable, this is not enough to motivate inactive adults to regularly engage in exercise and thereby improve health. Trial Registration: This study is registered at www.clinicaltrials.gov NCT03513380